Influence of the Tumor Microenvironment on Cancer Cells Metabolic Reprogramming - Gouirand, Victoire; Guillaumond, Fabienne; Vasseur, Sophie (Frontiers in Oncology, 2018)
As with castles, tumor cells are fortified by surrounding non-malignant cells such as cancer-associated fibroblasts, immune cells, but also nerve fibers and extra-cellular matrix. In most cancers, this fortification creates an important solid pressure which limits oxygen and nutrient delivery to the tumor cells and causes a hypoxic and nutritional stress. Consequently, tumor cells have to adapt their metabolism to survive and proliferate in this harsh microenvironment. In order to satisfy their need in energy and biomass, tumor cells develop new capacities to benefit from metabolites of the microenvironment, either by their uptake through the macropinocytosis process or through metabolite transporters, or by a cross-talk with stromal cells and capture of extracellular vesicles (EVs) that are released by the neighboring cells. However, the microenvironments of primary tumor and metastatic niches differ tremendously in their cellular/acellular components and available nutrients. Therefore, cancer cells must develop a metabolic flexibility conferring them the ability to satisfy their biomass and energetic demands at both primary and metastasis sites. In this review, we propose a brief overview of how proliferating cancer cells take advantage of their surrounding microenvironment to satisfy their high metabolic demand at both primary and metastasis sites.